Ação executiva lato sensu - Bronzatto, Alexandre Novelli (2006)
The objective of this dissertation is to examine the executive (lato sensu) action and doing so in three chapters. The first covers fundamental institutes for the comprehension of this kind of civil action. The study starts with a distinction between claim and action. Following is the traditional classifications of this juridic tutelage and of the process. Thus the systematization process of the juridic tutelage is formulated: cognition tutelage and tutelage of fisical repercussion. In that one are included the declaratory, constitutive and condemnatory sentence. In this, the injunctions and executive provision. At work the executive action is recognized, consisting in the reunion of cognitive activities and fisical repercussion in the same juridic processual relation. Taking in consideration the criterion of the evolved jurisdictional activity, the syncretic process is placed side by side with the trial procedure (which in Brazilian system doesn t includes the enforcement of the decision) and executive process. The second chapter starts with the examination of the actions and their classifications. Several execution concepts are then analyzed, as are the delimitations of the executives procedural structure and juridic nature. One tries to identify what they have in common, and the main distinction between the executive and the injunctions, rejecting the limitation of the first real execution. Finally, in the third chapter the aspects of the executive procedures are studies, emphasizing on the effectivity of the jurisdictional tutelage and the right to wide defence, both predicted in the 1988 Federal Constitution